Implementação da política de assistência estudantil: um estudo de três instituições federais de ensino superior localizadas no sul de Minas Gerais - Terra, Vitor Fernando (2015)
In recent years, the implementation of several access policies to IFES as REUNI, Quota system, ENEM, has supported the process of democratization of the brazilian higher education. From these policies the socioeconomic profile of the students of IFES has been significantly altered, when entering an increasingly larger number of students in socioeconomic vulnerability situation. In this context, it has been observed the need to consolidate within the IFES a Public Policy of Student Assistance (PPSA) to ensure the basic, conditions necessary to promote the effective permanence of these students until the completion of the course, through actions and programs, which have been given greater emphasis from the creation of the National Plan for Student Assistance (NPSA). This study was conducted in order to understand the process of implementation of the PPSA in three IFES located in south of Minas Gerais, Federal University of Alfenas (UNIFAL), Federal University of Itajubá (UNIFEI) and Federal University of Lavras (UFLA), comparing it amidst the IFES before and after the NPSA. The aim was also to identify the key actions and programs developed by each of the IFES studied. The theoretical framework addressed the themes: public policies, actors, the cycle of public policies with an emphasis on implementation phase, presenting the models top-dow, bottom-up and, finally, a brief history of implementation of the PPSA in IFES highlighting its evolution in the context of the Brazilian higher education. The methodology used was a qualitative approach. This was a descriptive study in which the method used was the case study. Primary data were collected through interviews, using semi-structured questionnaires applied to managers and servers of each IFES, directly linked to the implementation of the PPSA, in a total of 14 interviews. Secondary data have been also used such as institutional, documents and printed information available on the on line pages of each IFES. To analyze the data it was used the content analysis, in the thematic and documentary categories. The results revealed that the PPSA is understood as a mechanism of extreme importance within the IFES and that although it is noticed a breakthrough with the creation of NPSA the financial and human resources have been limiting factors to meet all demand. The NPSA, in turn, is correlated to other access policies, but is still in the design process. In the vision of respondents it is necessary that the actions and programs of PPSA have better disclosure, demystifying its understanding simply as being a form of welfare, going to be seen as a social right.